Construção de foguetes com garrafas pet para a mostra brasileira de foguetes (mobfog): uma proposta pedagógica utilizando gibi - Ferreira, João Paulo (Universidade Federal Rural do Semi-Árido, 2020)
Rockets were the first autonomous vehicles created by humans, wich, with the advances of science and technology, specially physics, made possible that modern rockets conquered the moon. Studying that is so marvelous, that in 1998 it was conducted the first Olimpíada Brasileira de Astronomia e Astronáutica (OBA), aiming the development of Science and inovation at schools. In 2007 the Mostra Brasileira de Foguetes (MOBFOG), came as a branche of the OBA, enabeling students’ team work, achieving amazing results such as the construction of PET rockets for a oblique launch competition. Having that experience as a inspiration, this research emerged from the attempt of instigating students, from the city of Rodolfo Fernandes, in the western of Rio Grande do Norte, to make their own rockets using PET bottles, preparing them to elaborate their manual. However, to reach that point, we started from specific objectives: i) take preparatory classes for the OBA admission test; ii) get a medal from the OBA test; iii) get enrolled on the rocket Building workshop and use the OBA’s manual available on their website; iv) participate on their school internal competition, seeking classification for the MOBFOG in Barra do Piraí – RJ and v) be admited at the MOBFOG and be a medalist. Accordingly to our methodology, the teacher’s role was to mediate students and knowledge, once that students were the first to get interested in this search to deepener their own knowledge. Resulting from our efforts, in the OBA event, we got a individual students’ bronze medal and in the MOBFOG, we had a silver medal as a team of three students, both competitions, as mentioned above, were in Rio de Janeiro
Keywords: Foguete; Garrafa PET; Ensino; Rockets; Pet bottle; Teaching; CIENCIAS EXATAS E DA TERRA::FISICA